Cloud-Based Centralizing system for academic history, plagiarism prevention management in Higher Education Institution IN DRC: Benefit, Challenges (British Journal of Multidisciplinary and Advanced Studies, 2022)
Cloud computing is becoming increasingly popular in the twenty-first century, with demand coming from all sectors of industry, including higher education institutions. In this paper, we address the benefits and limitations of cloud computing in the context of higher education institutions in DRC. Adopting modern cloud computing technology is projected to minimize the cost of IT-based solutions and services, as well as ICT infrastructure.  The purpose of this work is to establish a system on cloud based that will enable the centralization and exchange of data on students' academic careers, to prevent plagiarism, to avoid fraud and falsification of transcripts, Share the researches and academic works between the universities to avoid plagiarism. Many challenges must be resolved before cloud computing can be successfully deployed in higher education.